2013
DOI: 10.1080/14735903.2013.840436
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable agricultural intensification: the role of cardamom agroforestry in the East Usambaras, Tanzania

Abstract: The East Usambaras in Tanzania are a tropical biodiversity hotspot where current agricultural management practices pose threats to forest conservation and development objectives. Promoting sustainable agricultural intensification (SAI) would improve long-term productivity and reduce pressure on forest reserves. The study objective was to identify household-level characteristics that influence adoption of improved management practices, specifically soil replenishment practices, in order to identify opportunitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 69 publications
1
18
0
3
Order By: Relevance
“…Recently, Bullock et al (2013) measured the influence of socio-economic characteristics, physical and financial assets, tenure security and plot-specific attributes on the adoption of soil replenishment practices in cardamom agroforestry systems in the East Usambaras in Tanzania. A logistic regression analysis showed that marital status, household size, remittances, credit access and tenure security significantly affected the adoption of fallows and the application of organic inputs.…”
Section: Studies Focusing On Extrinsic Factorsmentioning
confidence: 99%
“…Recently, Bullock et al (2013) measured the influence of socio-economic characteristics, physical and financial assets, tenure security and plot-specific attributes on the adoption of soil replenishment practices in cardamom agroforestry systems in the East Usambaras in Tanzania. A logistic regression analysis showed that marital status, household size, remittances, credit access and tenure security significantly affected the adoption of fallows and the application of organic inputs.…”
Section: Studies Focusing On Extrinsic Factorsmentioning
confidence: 99%
“…Age plays a role for mulching and intercropping especially; indicating on the one hand that older farmers might be more risk-averse or less progressive in the uptake of innovative farming practices [14]. On the other hand it can be a proxy for the years the farm already settled on the same land, i.e., inducing an increased time of nutrient mining and thus increased requirement for investments into soil conservation [21]. A higher rate of time preference is positively related to mulching and indicates that the farmer is generally giving consumption now a higher value than future consumption [17].…”
Section: Discussionmentioning
confidence: 99%
“…They are better prepared and more willing to take a risk [21]. Smallholder farmers with few resources are likely to be highly risk-averse due to uncertainty [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age of farmers plays a significant role on the farmer's decision regarding conversion because younger farmers are expected to be more progressive and accepting of new farming techniques relative to older farmers [22,47]. The level of education is considered as an influencing factor.…”
Section: Analytical Framework For Data Analysismentioning
confidence: 99%